Бенчмаркінг як інноваційний інструмент аналізу академічних бібліотек - Оленич, Віолетта; Сокіл, Марія Богданівна (Видавництво Львівської політехніки, 2025)
The application of benchmarking technologies to analyze academic libraries allows for a systematic study of services and resources, identification of development directions, and implementation of new technologies. Benchmarking, as an innovative tool, allows you to conduct a comparative analysis of library activities, identify best practices and implement effective solutions.
Keywords: бенчмаркінг; академічні бібліотеки; бібліотечні сервіси; оцінювання якості; стратегічний розвиток; цифрова трансформація